Model colloids to study surface – ligand interactions in nanosized Fe3O4. (March 2019) - Maiorov, M M; Zablotsky, D; Blums, E; Krumina, A
Abstract: Using electrodispersion of metallic iron in an aqueous environment without additional reagents we create a chemically clean model system based on nanosized synthetic magnetite where the details of magnetic metal oxide – surfactant chemisorption can be studied by high fidelity magnetometry with nanometric precision. A comparative analysis of model colloidal solutions based on oleic acid and iron Fe 2+ oleate indicates a significant influence of the mode of surfactant adsorption on the magnetic diameter of the particles.